Hellenic Libraries Union Catalogue (HLUC) - Apostolaki, Marilia; Anastasopoulou, Christina; Veranis, George (Journal of Integrated Information Management, 2019)
Purpose - This is a descriptive paper highlighting the Hellenic Library Union Catalogue (HLUC) which is an information system that aims to integrate and highlight all the collections from the Greek libraries in one single catalogue. Design/methodology/approach – The HLUC information system was designed and developed by NTUA-HEAL-Link and the National Library of Greece. The approach used was to organize an open access collection of high-quality bibliographic data and the aim has been to promote, amongst other things, rare, special and other types of bibliographic material. The project is currently in a pilot phase. So far, more than 50 libraries from Greece and Cyprus are participating and the number of participants is increasing. Originality/value - The project responds to a real contemporary need of the entirety of the libraries, and will offer a service which will promote the history and the treasures of the Greek libraries, independently of their type, being public, or academic. Added value will be the integration of Inter-Library Loan Service with the HLUC.